Search task difficulty: the expected vs. the reflected - Liu, Jingjing; Belkin, Nicholas J (Association for Computing Machinery, 2011)
We report findings on how the user's perception of task difficulty changes before and after searching for information to solve tasks. We found that while in one type of task, the dependent task, this did not change, in another, the parallel task, it did. The findings have implications on designing systems that can provide assistance to users with their search and task solving strategies.
Keywords: Dependent tasks; Designing systems; Predicted difficulty; Reflected difficulty; Searching for informations; Task difficulty; Task type; User's perceptions; dept.ils